497 Late-Breaking: Low Number of Owner Reported Suspected Transmission of Foodborne Pathogens from Raw Meat-based Diets Fed to Dogs and/or Cats. (8th October 2021) - Cammack, Nicole R; Yamka, Ryan M; Adams, Vicki
Abstract: The aim of this worldwide survey was to determine owner reported frequency of pathogen transmission to humans living in or in contact with households feeding their pets commercial and homemade raw meat-based diets (RMBD). A total of 5, 611 responses were gathered from 62 countries with 77.1% of households feeding only RMBDs to dog(s) and/or cat(s) no confirmed cases of pathogen transmission or infection by laboratory testing. Eleven households (0.20%, 95%CI: 0.10 – 0.36) were classified as having experienced 'probable' transmission and 20 households (0.36%, 95%CI: 0.22 – 0.56) were classified as having experienced "possible" transmission to result in a total of 31 households (0.55%, 95%CI: 0.38 – 0.79) being identified as potential cases of transmission (fig. 1). The remainder of households (n = 5, 580 = 99.45%, 95% CI: 99.21 – 99.62) were not considered to have experienced potential transmission of foodborne pathogens based on their responses to the survey. The most frequently reported pathogens were Salmonella (n = 11, 0.2%), Campylobacter (n=6, 0.1%) and E. Coli (n = 4, 0.1%), with the most common age group being adults age 18–65 (n=29, 78.4% of cases). Beef and chicken were the most common proteins reported as being fed in case households although this was not associated with pathogen transmission. Households feeding a greater number of different protein sources, including pork, turkey, duck, rabbit and salmon, were associated with decreased risk of pathogen transmission. Additional risk factors associated with pathogen transmission included preparing RMBD in a separate location, with different utensils than human food (fig. 2), mixing RMBD with dry (kibble) diets and feeding a limited variety of protein sources. Based on the results of this survey, confirmed pathogen transmission from RMBD to humans appears to be rare. We conclude that potential or probable cases of pathogen transmission is likely dependent upon hygiene and food safety measures and more education surrounding food safety should reduce risk.